Challenges in Clinicogenetic Correlations: One Gene – Many Phenotypes. Issue 3 (2nd March 2021) - Magrinelli, Francesca; Balint, Bettina; Bhatia, Kailash P.
ABSTRACT: Background: Progress in genetics – particularly the advent of next‐generation sequencing (NGS) – has enabled an unparalleled gene discovery and revealed unmatched complexity of genotype–phenotype correlations in movement disorders. Among other things, it has emerged that mutations in one and the same gene can cause multiple, often markedly different phenotypes. Consequently, movement disorder specialists have increasingly experienced challenges in clinicogenetic correlations. Objectives: To deconstruct biological phenomena and mechanistic bases of phenotypic heterogeneity in monogenic movement disorders and neurodegenerative diseases. To discuss the evolving role of movement disorder specialists in reshaping disease phenotypes in the NGS era. Methods: This scoping review details phenomena contributing to phenotypic heterogeneity and their underlying mechanisms. Results: Three phenomena contribute to phenotypic heterogeneity, namely incomplete penetrance, variable expressivity and pleiotropy. Their underlying mechanisms, which are often shared across phenomena and non‐mutually exclusive, are not fully elucidated. They involve genetic factors (ie, different mutation types, dynamic mutations, somatic mosaicism, intragenic intra‐ and inter‐allelic interactions, modifiers and epistatic genes, mitochondrial heteroplasmy), epigenetic factors (ie, genomic imprinting, X‐chromosome inactivation, modulation of genetic and chromosomal defects), and environmental factors. Conclusion: Movement disorders is unique in its reliance on clinical judgment to accurately define disease phenotypes. This has been reaffirmed by the NGS revolution, which provides ever‐growing sequencing data and fuels challenges in variant pathogenicity assertions for such clinically heterogeneous disorders. Deep phenotyping, with characterization and continual updating of "core" phenotypes, and comprehension of determinants of genotype–phenotype complex relationships are crucial for clinicogenetic correlations and have implications for the diagnosis, treatment and counseling.